#### Answer

$f(3)=-15$

#### Work Step by Step

To find $f(3)$, substitute 3 to $x$ in $f(x)$ to obtain:
$f(x) =-2x^2+3x-6
\\f(3)=-2(3)^2+3(3)-6
\\f(3)=-2(9)+9-6
\\f(3)=-18+9-6
\\f(3)=-9-6
\\f(3)=-15$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$f(3)=-15$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.